Розробка скриптів для обробки даних та створення звітів - Казанцева, С. С. (ХНУРЕ, 2023)
In today's world, the increase in the amount of data generated every day requires fast and efficient data processing. Developing scripts for processing data and creating reports is becoming a necessity for most companies and individual users. This talk will cover the basic aspects of scripting for data processing and report generation.